SNP Discovery and Genetic Variation of Candidate Genes Relevant to Heat Tolerance and Agronomic Traits in Natural Populations of Sand Rice (Agriophyllum squarrosum) - Zhao, Pengshan; Zhang, Jiwei; Qian, Chaoju; Zhou, Qin; Zhao, Xin; Chen, Guoxiong; Ma, Xiao-Fei (Frontiers in Plant Science, 2017)
The extreme stress tolerance and high nutritional value of sand rice (Agriophyllum squarrosum) make it attractive for use as an alternative crop in response to concerns about ongoing climate change and future food security. However, a lack of genetic information hinders understanding of the mechanisms underpinning the morphological and physiological adaptations of sand rice. In the present study, we sequenced and analyzed the transcriptomes of two individuals representing semi-arid (Naiman, NM) and arid (Shapotou, SPT) sand rice genotypes. A total of 105,868 pairwise SNPs distributed in 24,712 Unigenes were identified among SPT and NM samples; the average SNP frequency was 0.3% (one SNP per 333 base pair). Characterization of gene annotation demonstrated that variations in genes involved in DNA recombination were associated with the survival of the NM population in the semi-arid environment. A set of genes predicted to be relevant to heat stress response and agronomic traits was functionally annotated using the accumulated knowledge from Arabidopsis and several crop plants, including rice, barley, maize, and sorghum. Four candidate genes related to heat tolerance (heat-shock transcription factor, HsfA1d), seed size (DA1-Related, DAR1), and flowering (early flowering 3, ELF3 and late elongated hypocotyl, LHY) were subjected to analysis of the genetic diversity in ten natural populations, representing the core germplasm resource across the area of sand rice distribution in China. Only one SNP was detected in each of HsfA1d and DAR1, among 60 genotypes, with two in ELF3 and four in LHY. Nucleotide diversity ranged from 0.00032 to 0.00118. Haplotype analysis indicated that the NM population carried a specific allele for all four genes, suggesting that divergence has occurred between NM and other populations. These four genes could be further analyzed to determine whether they are associated with phenotype variation and identify alleles favorable for sand rice breeding.